2018
DOI: 10.1016/j.jtho.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib and Cetuximab in Four Patients With EGFR Exon 20 Insertion–Positive Advanced NSCLC

Abstract: Dual EGFR blockade with afatinib and cetuximab may induce tumor responses in patients with EGFR exon 20 insertion-positive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…79,81 More recently, a clinical study found that three out of four EGFR exon 20 insertion-positive NSCLC patients had partial responses to a combination of afatinib and cetuximab, with a median PFS of 5.4 months. 82 These results suggest that the cetuximab and EGFR inhibitor combination may have some efficacy in patients with exon 20 insertions; however, with limited clinical data, further work is necessary to determine the impact of the insertion size and location on the response to cetuximab combinations.…”
Section: Treatment Options For Egfr Exon 20 Insertion Nsclcmentioning
confidence: 96%
“…79,81 More recently, a clinical study found that three out of four EGFR exon 20 insertion-positive NSCLC patients had partial responses to a combination of afatinib and cetuximab, with a median PFS of 5.4 months. 82 These results suggest that the cetuximab and EGFR inhibitor combination may have some efficacy in patients with exon 20 insertions; however, with limited clinical data, further work is necessary to determine the impact of the insertion size and location on the response to cetuximab combinations.…”
Section: Treatment Options For Egfr Exon 20 Insertion Nsclcmentioning
confidence: 96%
“…Increased exposure of the malignant cells to different anticancer agents amplifies the heterogeneity of the tumor and several overcoming therapies against drug resistance are proposed [139]. These include (i) combination therapy against single target (i.e., TKI afatinib against EGFR and monoclonal antibody cetuximab against EGFR) [150] or against multiple targets (i.e., a third generation TKI of EGFR(T790M) and navitoclax an inhibitor of ABC transporters) [151]; (ii) sequential therapy to reduce the toxicity induced by combination of chemotherapeutic agents [152] or (iii) targeted therapy after identification of genetic markers (i.e., patients with EGFR(T790M) mutation which can benefit from osimertinib treatment compared to patients with activating mutations in EGFR who can benefit by gefinitib/erolotinib/afatinib administration) [153]. New experimental studies and different therapeutic approaches are required to find the optimal way to interfere with development of tumor malignancy.…”
Section: Tumor Heterogeneitymentioning
confidence: 99%
“…Two patients carrying EGFR D770_P772delinsKG and EGFR D770>GY, respectively, were treated with one such antibody-cetuximab--as part of their regimen, and achieved ongoing partial response at 6+ and 42+ months [9]. In another study, 3 of 4 patients receiving cetuximab combined with afatinib also achieved responses [10]. This strategy has been explored in ErbB2/HER2 exon 20 mutation-positive patients: a trastuzumab-based regimen combined with lapatinib showed remarkable tumor regression in a case of metastatic lung adenocarcinoma [11].…”
Section: Therapeutic Approaches Aimed At Egfr Exon 20 Insertions In Lmentioning
confidence: 99%